2003
DOI: 10.1655/0018-0831(2003)059[0119:ansots]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Tantilla (Serpentes: Colubridae) From Southeastern Brazil

Abstract: We describe a new species of Tantilla (Serpentes: Colubridae) from the highlands (''campos rupestres'') of the Serra do Cipó , Minas Gerais, southeastern Brazil. The new species belongs in the T. melanocephala group and is characterized by its uniform reddish orange dorsum with no dark middorsal stripe, a broad pale nuchal band medially divided, and a dark head cap without posterior lateral extensions. Color photographs of adult individuals and illustration of hemipenes of both the new species and T. melanocep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
1
12
0
2
Order By: Relevance
“…The records of the species listed in red lists per se points out that Serra do Cipó National Park is an important protection area for mammals. The importance of Serra do Cipó National Park to the Cerrado Biome was already evidenced for many groups of invertebrates and vertebrates (Lara and Fernandes 1997;Eterovick and Fernandes 2001;Melo-Junior et al 2001), with the description of several new species of mammals, reptiles, and amphibians, based on specimens collected in this park (Sazima et al 1978;Sawaya and Sazima 2003;Pugliese et al 2004). For mammals we can highlight the description of the bat Lonchophyla bokermanni (Sazima et al 1978), which is listed as Endangered in the state's red list (Biodiversitas 2007) and considered as Data Deficient worldwide (IUCN 2011).…”
Section: Resultsmentioning
confidence: 98%
“…The records of the species listed in red lists per se points out that Serra do Cipó National Park is an important protection area for mammals. The importance of Serra do Cipó National Park to the Cerrado Biome was already evidenced for many groups of invertebrates and vertebrates (Lara and Fernandes 1997;Eterovick and Fernandes 2001;Melo-Junior et al 2001), with the description of several new species of mammals, reptiles, and amphibians, based on specimens collected in this park (Sazima et al 1978;Sawaya and Sazima 2003;Pugliese et al 2004). For mammals we can highlight the description of the bat Lonchophyla bokermanni (Sazima et al 1978), which is listed as Endangered in the state's red list (Biodiversitas 2007) and considered as Data Deficient worldwide (IUCN 2011).…”
Section: Resultsmentioning
confidence: 98%
“…However, it is possible that the name Tantilla pallida Cope, 1887, synonymized to T. melanocephala by Wilson & Mena (1980), is applicable to the Cerrado forms (Sawaya & Sazima 2003).…”
Section: Taxonomic Remarksmentioning
confidence: 99%
“…Its color pattern, with a live red dorsum, a white nuchal band, and a black head (Figure 24), may be considered as mimetic of coral snakes (cf. Savage & Slowinsky 1992, Sawaya & Sazima 2003. Indeed, this pattern was less preyed upon (i. e., protected) than controls in experiments with clay models in Costa Rica (Brodie 1993). 14.…”
mentioning
confidence: 91%
“…Reviewing published information on morphological characteristics of all other species of the genus Tantilla (Wilson, 1987;Sawaya & Sazima, 2003;Townsend et al, 2013;Wilson & Mata-Silva, 2014; revealed that the collected specimens can be easily differentiated from others of the genus by its comparatively high number of ventral scales and other scalation characteristics, its relatively large size, and transversely-banded color pattern. Herein a detailed description of the new species is given.…”
Section: Introductionmentioning
confidence: 99%